It is a substitution problem

(1) y = **-3x + 5 **

(2) 5x - 4y = -3

Substitute eqn 1 into eqn 2 for y. (It doesn't matter which eqn or which variable, but eqn 1 was already solved for y.)

5x - 4(**-3x + 5**) = -3

Simplify, and solve for x.

5x +12x -20 = -3

17x - 20 = -3

17x = 17

x = 1

Now substitute the value of x into eqn 1 (again, it doesn't matter but eqn 1 is convenient).

y = -3(1) + 5 = -3 + 5 = 2

So, x = 1, y = 2; i.e., the graphs share a common solution (or intersect) at the point (1,2).